Entrepreneurship education: A systematic literature review of curricula contents and teaching methods - Fatima Sirelkhatim; Yagoub Gangi (Cogent Business & Management, 2015)
Entrepreneurship education (EE) is one of the fastest growing fields of education globally, yet the areas of “what” should be taught in these programmes and “how” to teach them have been mentioned by many researchers as ones that lack both consensus and devoted attention. The present paper aims to provide a detailed map of common and best practices in terms of curriculum content and methods of teaching entrepreneurship on the tertiary level, and to explore how they correlate with practices recommended by the entrepreneurial learning field of research, in order to contribute to extracting best practice. This paper uses a systematic literature review (SLR) to help review the literature in a transparent and unbiased way. The review is undertaken through six stages using NVivo computer software. In each stage, the literature on EE is screened and filtered to reduce the size and try to reach the more relevant and useful papers. This process end up with 129 articles divided between EE and entrepreneurship learning. The result of the reviewing process reveals that the curricula content and teaching methods vary depending on the programme's objectives—from theoretical courses aiming to increase entrepreneurial awareness to practical-oriented ones that aim to produce graduates ready to start a business. Practical-oriented courses correlate with entrepreneurial learning suggestions for practices to engage students in acquiring entrepreneurial competencies. However, to better extract best practice, it would be useful if future research could explore what, exactly, it is that we mean when we use the term “entrepreneurial course” and link it to the entrepreneurship process. Also, it would be useful to explore what are the results of EE programmes in terms of the actual graduates who start or grow a business, and link the findings to the teaching process.
Keywords: 650